The Effect of Online Learning on Student Learning Outcomes and Interests in Islamic Education Subjects at Senior High School - Khairial Khairial; Syamsu Nahar; Siti Halimah (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to see: 1) The influence of online learning on the learning outcomes of Islamic Religious Education students in the Senior High School of the Kedai Sianam Family Education Foundation; 2) The influence of online learning on students' interest in learning Islamic Religious Education in the Kedai Sianam Family Education Foundation High School; 3) The interaction between online learning and students' interest in learning in influencing the learning outcomes of Islamic Religious Education in the Senior High School of the Kedai Sianam Family Education Foundation. This research uses quantitative research type of experiment with the design used is True Experimental using the form of The Randomized Pretest-Posttest Control Group Design. The study sample was 64 students with details that the experimental class was 31 people and the control class was 33 people. There is an influence of online learning on the learning outcomes of students of SMA YPK Kedai Sianam. Then there is the influence of online learning on the learning interests of students of SMA YPK Kedai Sianam. This can be seen from the average score of high student interest in learning through online learning (®= 21.12) as a whole higher than the average interest in learning Islamic Religious Education (IRE) of YPK Kedai Sianam High School students with low interest in learning (®= 17.81). There is an interaction between online learning and interest in learning in influencing the learning outcomes of IRE students of SMA YPK Kedai Sianam. This is evidenced by Fcount = 18.307 and Significance of 0.001. Sig Value. 0.001 is known to be smaller than 0.05 (0.001 0.05), so the hypothesis can be accepted and empirically proven in this study.